2018
DOI: 10.1371/journal.pone.0205447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sensor location on continuous intraperitoneal glucose sensing in an animal model

Abstract: BackgroundIn diabetes research, the development of the artificial pancreas has been a major topic since continuous glucose monitoring became available in the early 2000’s. A prerequisite for an artificial pancreas is fast and reliable glucose sensing. However, subcutaneous continuous glucose monitoring carries the disadvantage of slow dynamics. As an alternative, we explored continuous glucose sensing in the peritoneal space, and investigated potential spatial differences in glucose dynamics within the periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Experiments under anaesthesia will inevitably affect the pig’s physiology and influence the data. Prolonged IV infusion of fluids can lead to increased production of IP fluid in pigs 37 , 38 . The IP space can potentially hold several litres, while under normal conditions it contains only small amounts of IP fluid 39 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments under anaesthesia will inevitably affect the pig’s physiology and influence the data. Prolonged IV infusion of fluids can lead to increased production of IP fluid in pigs 37 , 38 . The IP space can potentially hold several litres, while under normal conditions it contains only small amounts of IP fluid 39 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Fluid balance was achieved by continuous IV infusion of Ringer's acetate, approximately 1,000 ml during the length of the experiment, with individual adjustments. The described anaesthesia protocol have been used in previous pig experiments 37 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine samples of intraperitoneal fluid was collected from two pigs during unpublished pilot experiments (date: 6 June 2019 and 11 June 2019, kept frozen) performed similarly to other work from our group [36,37]. The intraperitoneal fluid samples were spiked with glucose and lactate in powder form to avoid diluting the fluid.…”
Section: Verification Using Biological Samplesmentioning
confidence: 99%
“…Peritoneal fluid, which lubricates the organ surfaces in the peritoneal space, contains glucose in similar concentrations to the BGL. Promising short-term studies with intraperitoneal (IP) glucose sensing using electrochemical sensors have been reported [22], and some preliminary data from recent long-term studies have been demonstrated [23]. These studies have shown faster glucose sensing dynamics in the peritoneal space compared to SC sites, indicating that the intraperitoneal space may be a better site for a fully automated AP.…”
Section: Introductionmentioning
confidence: 99%